Peningkatan Numerasi dan Berpikir Kritis Anak Usia 4–5 Tahun: Studi Kuasi-Eksperimen di TK Al Fatah Sedan Melalui Media Permainan Lompat Angka - Rani Puspita Sari; Winarti Winarti (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study examines whether the number jumping game media (LANGKA) is associated with improvements in numeracy literacy and critical thinking skills among children aged 4–5 years in a single kindergarten context.Methods – This quantitative quasi-experimental study employed a Non-Equivalent Control Group pretest–posttest design using two intact classes (n = 34) at TK Al Fatah Sedan, Yogyakarta. The experimental group received the LANGKA intervention, while the control group used worksheet-based activities. Primary outcome data were collected using structured observations with validated rubrics; interviews and documentation were used as supporting data to describe implementation and learning context. Data analysis included assumption tests and baseline (pretest) checks. Between-group differences were examined using gain scores (posttest–pretest) with an independent-samples t-test, complemented by effect size estimates (Cohen’s d).Findings – The experimental and control groups differed significantly on numeracy literacy and critical thinking outcomes (p < .001). The standardized differences were large (Cohen’s d = 2.85 for numeracy literacy; 2.24 for critical thinking). These results should be interpreted cautiously due to the non-randomized, single-site design. Research Implications – Practically, kinesthetic game-based media such as LANGKA can be considered as an alternative approach to integrate motor activity with early numeracy and critical thinking stimulation in classroom routines. Limitations include the non-randomized design and single-site context; further studies with larger samples, multi-site settings, and stronger baseline control (e.g., ANCOVA) are recommended.